Further Studies on Seed Production in Sal (Shorea robusta Gaertn.) Crops in Dehra Dun District (U.P.). - Sharma, B. K. (Indian Forester, 1981)
Field data regarding production and collection of sal (Shorea robusta Gaertn.) seed in Dehra Dun forests during the years 1978 and 1979, subsequent to the bumper crop year 1977, have been reported. It is observed that bumper crop year is followed by a poor/lean seed year and then by a good/moderate seed year. The minimum quantities of sal seed available per hectare from young to middle-aged and middle-aged to mature crops for these two years along with the optimum time and period of collection are reported.